Simulating particle acceleration in rippled space plasma shocks - Sjöblom, Frans (My University, 2020)
Plasma shocks are one of the key mechanisms accelerating particles to high energies. Although the theory behind diffusive shock acceleration is well known, there are unexplained differences in the observed particle spectra of different shock geometries. Recently with multispacecraft missions like Cluster, Time History of Events and Macroscale Interactions during Substorms (THEMIS), and Magnetospheric Multiscale (MMS) have made it possible to study the deformations (ripples) of the shock surface. Due to the high cost of satellite missions, computer simulations are also used to study the features of particle acceleration. Simulations range from kinetic schemes, where each particle is followed, to fluid models, where the whole plasma population is approximated as a single fluid. Choosing the correct simulation method is essential for studying specific features of shock acceleration. A Monte Carlo test particle simulation code is developed in this thesis to study the features of ripples in isolation. The key finding is that a quasi-parallel shock appears to be able to accelerate particles as efficiently as a quasi-perpendicular shock when the shock surface is fully rippled. The results indicate that the time the ripple is present at the shock surface determines the efficiency of the particle acceleration. The size of the ripple seems to define the maximum achievable acceleration. The results highlight the importance of the deformation of the shock surface to particle acceleration. In the future, the results of these simulations should be compared with satellite observations and parameter combinations should be explored with the simulation code.

Plasmashokit pystyvät kiihdyttämään hiukkasia suuriin energioihin. Shokkigeometriasta riippuen hiukkasten energiaspektreissä on huomattavia eroja teorian ja havaintojen välillä. Viime aikoina modernit satellittihankkeet, kuten Cluster, Time History of Events and Macroscale Interactions during Substorms (THEMIS) ja Magnetospheric Multiscale (MMS), ovat mahdollistaneet shokkipinnan epätasaisuuden tutkimuksen. Satelliittien kalliin hinnan takia myös tietokonesimulaatiota käytetään plasman tutkimuksessa. Simulaatioiden skaalat vaihtelevat hyvin tarkoista kineettisistä malleista nestemalleihin. Kineettisissä simulaatioissa mallinnetaan tarkasti hiukkasten ratoja ja niiden vaikutusta sähkömagneettisiin kenttiin, kun taas nestemalleissa plasma yleistetään yhdeksi kollektiivisesti käyttäytyväksi nesteeksi. Shokkikiihdytyksen yksittäisten ominaisuuksien tutkimuksessa oikean simulaatiomenetelmän valinta on erityisen tärkeää. Tutkielmassa kehitettiin Monte Carlo testipartikkelisimulaatio, jonka avulla pystyttiin yksitellen tutkimaan eri shokkipinnan epätasaisuuksien ominaisuuksien vaikutusta. Tutkielman tulokset antavat ymmärtää, että lähes pitkittäinen shokkipinta pystyy kiihdyttämään partikkeleita lähes poikittaisen shokin tyylisesti, kun pitkittäisen shokin pinta on täysin väreilevä. Tulokset osoittavat, että hiukkaskiihdytyksen tehokkuus määrittyy sen mukaan, kuinka usein pinta väreilee. Shokkipinnan väreilyn amplitudi vaikuttaa partikkelien suurimpaan mahdolliseen saavutettavaan energiaan. Tulokset korostavat shokkipinnan väreilyn vaikutusta partikkelien kiihdytykseen. Jatkossa simulaatiotuloksia tulisi verrata havaintoihin ja simulaatiolla tulisi tutkia eri parametriyhdistelmien vaikutusta shokkikiihdytyseen.
Keywords: space physics, particle acceleration, shock, ripple, simulation, Monte Carlo, test particle